Development and Psychometric Properties of Self-Advocacy for Women Experiencing Intimate Partner Violence Scale - Kaewsawang, Tonsai; Kramanon, Sittiporn; Intaraprasert, Dussadee (Journal of Behavioral Science for Development, 2023)
The main purpose of this study was to develop and test the psychometric properties of the Self-advocacy for Women Experiencing Intimate Partner Violence Scale. The scale was constructed based on related theories. The developed scale was then tested for content validity by experts. The participants were 400 women who experiencing intimate partner violence that treated by One Stop Crisis Center (OSCC) affiliated with hospitals in Thailand. In process of construct validity testing the researcher randomly divided the sample into 2 groups (200 sample per group). First, analyze the 1st group data by exploratory factor analysis then analyze the 2nd group by confirmatory factor analysis. Results of exploratory factor analysis indicated that the Self-Advocacy for Women Experiencing Intimate Partner Violence Scale consisted of 22 items with 3 factors (KMO = .894): ‘Knowledge of self’, ‘Leadership and knowledge of right’ and ‘Communication skills’. These 3 factors accounted for 53.135% of the total variance. Results of confirmatory factor analysis indicated that the Self-advocacy for Women Experiencing Intimate Partner Violence Scale consisted of 3 components that measured all 22 observed variables. The result found that standard factor loading between 0.440 - 0.960 at 0.01 level. And goodness of fit with the empirical data were (c2 = 90.318, df = 139, Relative Chi-square = .650, P = 1.000, RMSEA = 0.000 RMR = 0.058, GFI = 0.961, CFI = 1.000, PGFI = 0.582 respectively. So, The Self-advocacy for Women Experiencing Intimate Partner Violence Scale had good psychometric properties in terms of validity and reliability that reflected three elements of self – advocacy. It can be used to assess and cultivate self – advocacy in women who experiencing intimate partner violence.